2017
DOI: 10.3329/jesnr.v10i1.34689
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heavy Metal Contamination in Fishes from Passur River near the Sundarbans Mangroves of Bangladesh

Abstract: The study was conducted to investigate the heavy metal contamination in fishes and shrimps from the Passur River near the world famous Sundarban mangroves located in the southwestern part of Bangladesh, during the period from January to June 2013. The fish (Liza parse) and shrimp (Penaeus monodon) samples were collected from two stations as St-1 (Katakhali-1 km upper from port areaupstream) and St-2 (Amtola-1 km lower from port area-downstream) monthly for three months in January (winter), March (pre monsoon) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Usually, the highest DO (7.06 mg/L) was found in monsoon and the lowest DO (6.04 mg/L) was observed in pre-monsoon season (Table 2). When dissolved oxygen becomes too low, fish and other aquatic organisms cannot survive (Islam et al, 2017). Nahian et al (2018) found their study in Gowain River the mean concentration of DO was 4.86, 5.18 and 4.42 mg/L in premonsoon, monsoon and post-monsoon season, respectively.…”
Section: Total Dissolved Solid (Tds)mentioning
confidence: 96%
“…Usually, the highest DO (7.06 mg/L) was found in monsoon and the lowest DO (6.04 mg/L) was observed in pre-monsoon season (Table 2). When dissolved oxygen becomes too low, fish and other aquatic organisms cannot survive (Islam et al, 2017). Nahian et al (2018) found their study in Gowain River the mean concentration of DO was 4.86, 5.18 and 4.42 mg/L in premonsoon, monsoon and post-monsoon season, respectively.…”
Section: Total Dissolved Solid (Tds)mentioning
confidence: 96%
“…Excessive nitrite may accumulate in the blood of some fish species and, among other things, cause the oxidation of iron in hemoglobin producing methemoglobin, which is not capable of transporting oxygen (Islam et al, 2017). The concentrations of NO2-N at four stations were within the range of 0.01 (at St-2 along the study period) to 0.04 mg/L (at St-1 along with St-4 during monsoon) (Table 2).…”
Section: Nitrite (No2-n)mentioning
confidence: 98%
“…Oxygen is also introduced into the water as a byproduct of aquatic plant photosynthesis. When dissolved oxygen becomes too low, fish and other aquatic organisms cannot survive (Islam et al, 2017). The DO of the water at the four stations ranged from 6.1 to 7.65 mg/L.…”
Section: Physiochemical Water Qualitymentioning
confidence: 99%
“…Md. Sirajul Islam, Yousuf Ali, M. Humayun Kabir, Rofi M. Zubaer, Nowara Tamanna Meghla, Mausumi Rehnuma, Mir M. Mozammal Hoque (Islam et al, 2017;Islam et al, 2019). Thus, the nutrient concentration must be within suitable limit for a good aquatic environment and for better production of aquatic organisms (Rahaman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%